Hepatocyte and Islet Cell Cotransplantation on Poly-L-Lactide Matrix for the Treatment of Liver Cirrhosis. (14th October 2020) - Hendrawan, Siufui; Lheman, Jennifer; Nuraeni,; Weber, Ursula; Baer, Hans Ulrich
Abstract : The human autologous hepatocyte matrix implant is a promising alternative procedure to counter liver damage. We assessed the outcome of human hepatocytes isolation from cirrhotic liver compared to the clinical and histological scores of disease severity. A total of 11 patients with various clinical scores (CTP and MELD) and histological score (Metavir, fibrosis) of liver cirrhosis were included in the hepatocyte matrix implant clinical phase I study. The liver segment and pancreatic tissue were harvested from each patient, and hepatocytes and cells of islets of Langerhans were isolated. The freshly isolated human hepatocytes were coseeded with the islet cells onto poly(l-lactic acid) (PLLA) scaffolds, cultured, and transplanted back into the patient. Human hepatocytes were isolated from 11 cirrhotic liver specimens with a resulting yield of 1.4 ± 0.5 × 10 6 cells per gram of the liver specimen and a viability rate of 52 ± 13%. It was found that the yield and viability of the liver cells were not correlated with the clinical and histological scores of the liver cirrhosis. A correlation was found between the hepatocyte yield obtained and the average number of hepatocytes counted in 10 microscopic fields of view. More viable cells were obtained from cirrhotic livers caused by chronic hepatitis B as compared to chronic hepatitis C in the same MELD score range. There was no correlation between the clinical and histological disease severity scores of liver cirrhosis and the outcome of hepatocytes isolation. It seems that the yield could depend on the type of hepatitis underlying the cirrhotic tissue. The study was registered at www.clinicaltrial.gov with the study identifier: NCT01335568 .